Application of the Problem Solving Method to improve the Mental Attitude of Students in Islamic Education Subjects at SD Negeri Lubok Pasi Ara - Rosniar (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to determine the effectiveness of the Problem Solving method in improving students' mental attitudes in Islamic Religious Education at SD Negeri Lubok Pasi Ara. This study was conducted to determine whether the use of Problem Solving can improve students' motivation, engagement, critical thinking skills, and emotional resilience. This study used a quasi-experimental design, with the experimental group implementing the Problem Solving method and the control group following the traditional teaching method. Data were collected through pretest and posttest, classroom observation, and qualitative feedback from students. The findings of the study revealed that the experimental group showed significant improvements in motivation, critical thinking, and emotional resilience compared to the control group. Students who participated in the Problem Solving activity showed greater engagement, active participation, and collaboration. In addition, students showed improvements in social interaction, communication skills, and problem-solving abilities. The control group, on the other hand, showed minimal changes in their mental attitudes, highlighting the effectiveness of the Problem Solving method in fostering a more dynamic and positive learning environment. This study concludes that the Problem Solving method is an effective approach to improving students' mental attitudes in Islamic Education. By encouraging active learning, critical thinking, and collaboration, this method provides students with a meaningful and engaging learning experience. The results of the study suggest that educators should consider integrating Problem Solving strategies into their teaching to improve student motivation and overall learning outcomes. Further research is recommended to explore the long-term impact of this method on students’ academic performance and personal development.